MATERIALS FOR AUTOMOTIVE INDUSTRY AND THEIR INFLUENCE ON THE DYNAMICS OF A CAR CRASH - NICOLAE NAVODARIU; ROBERT CIOCOIU; OCTAVIAN TRANTE; VASILE IULIAN ANTONIAC (Journal of Engineering Studies and Research)
The aim of this research was to determine the influence of the metallic materials characteristics on the dynamics of a car crash. Another important aspect is that the metallic parts are sometimes repaired after minor accidents and this fact influence strongly the mechanical characteristics and their influence on the dynamics of a car crash. In this paper, we analyze the mechanical characteristics of thin steel plates repaired by local heating associated with plastic deformation (similar to hot working) and cold straightening (similar to local cold working) for automotive side and door panels made of structural steel. Thin sheet plates, 0.9mm thickness, were deformed by impact and repaired by local heating using the flame and induction heating then plastically deformed while hot as well as straightened without heating. The heat repaired samples were studied by light microscopy to determine microstructure change and samples were tensile tested to determine their mechanical characteristics. Local excessive grain growth generates anisotropy, the assembly behaves as a composite material with regions that show significant plastic deformations while others little or no deformations at all. Without procedures adjusted to each material repairs involving heating are to be avoided, cold working should be employed when replacement is not possible.